2004
DOI: 10.1177/00224669040380010201
|View full text |Cite
|
Sign up to set email alerts
|

The Supply of and Demand for Special Education Teachers

Abstract: There is a critical shortage of special education teachers in the United States. This shortage is chronic and severe and exists in every geographic region of the nation. This article provides an analysis of factors influencing the supply of and demand for special education teachers. Initially, the magnitude of this shortage is addressed, considering variances that exist by personnel type, locality, and job description. This is followed by an analysis of trends in the supply of and demand for special education … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 161 publications
(34 citation statements)
references
References 28 publications
0
30
0
Order By: Relevance
“…Even though a great deal of funding has been invested in PDs to improve in-service teacher practice, pedagogies in real classrooms have not changed as much as expected (McLeskey, 2011). What teachers learn from PD and what and how much they actually enact in their classrooms might differ (Pfeffer & Sutton, 2000).…”
Section: Contribution Of This Paper To the Literaturementioning
confidence: 99%
See 2 more Smart Citations
“…Even though a great deal of funding has been invested in PDs to improve in-service teacher practice, pedagogies in real classrooms have not changed as much as expected (McLeskey, 2011). What teachers learn from PD and what and how much they actually enact in their classrooms might differ (Pfeffer & Sutton, 2000).…”
Section: Contribution Of This Paper To the Literaturementioning
confidence: 99%
“…What teachers learn from PD and what and how much they actually enact in their classrooms might differ (Pfeffer & Sutton, 2000). An expert-centered PD, compared to a learnercentered PD, rarely enabled changes in teaching practices to be realized (McLeskey, 2011). The expertcentered setting indicated a PD that was provided by an outside specialist, who was well known within reformed education (Choy, Chen, & Bugarin, 2006), and teachers were given knowledge on the innovative instructional approaches passively.…”
Section: Contribution Of This Paper To the Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…McLeskey (2005) reviewed the limited amount of statistics available on the three types of turnover of SETs and concluded that "These statistics reveal an extraordinarily high level of instability in the special education teaching profession, resulting in teachers moving in and out of special education classrooms at a disquieting rate" (p. xvii). In view of inadequacies in turnover data for SETs, he stated that more recent data and more extensive data are needed on the turnover of SETs-especiaily on the transfer of SETs to teaching positions in general education (McLeskey, Tyler, & Flippin, 2004). Accordingly, this research investigated trends during a recent 9-year period in each of the three types of teacher turnover (attrition, teaching area transfer, migration), separately for SETs and GETs, using national data produced by the TFSs for 1991-1992, 1994-1995, and 2000-2001. These analyses addressed the main issues in turnover reviewed previously and were conducted with TFS data by the same methods to enable valid comparisons among them.…”
Section: Turnovermentioning
confidence: 99%
“…Kochhar et al (2000) inferred from their studies that the main difficulty with integration in the USA tends to relate to organisation and attitude barriers, as well as the lack of knowledge of teachers. Similarly to what has happened in Spain, McLeskey et al (2004) critically analysed the lack of teachers involved in special education in the USA. They conclude that the reason for this is the low engagement of pupils in school, the poor outcome of education programmes for these groups and the insufficient funding of the required necessities derived from the inadequate 'implantation of inclusion'.…”
Section: Recent Research and Studiesmentioning
confidence: 99%